Textual narrative and visual imagery themes portrayal in Isis's Rumiyah magazine issue 1 / Rabiatul Kamsina Md Yusof and Mokhtar Muhammad - Md Yusof, Rabiatul Kamsina; Muhammad, Mokhtar (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2019)
ISIS is one of the top extremist radical terrorist group in today's era. Their extreme action of jihad and radical Islamic fundamentalist ideology attract many believers to follow their path. The number of their followers shows a significant increasing of number recruited from many countries has threatened the global community. The results of this study would provide insights into the propaganda tools use by ISIS as their strategic psychological warfare to attract potential followers through their online digital magazine, titled 'Rumiyah'. This study observed and analysed the common textual narratives and visual imagery theme use by ISIS in their first Rumiyah issue. The content analysis of descriptive qualitative approach were used to analyse the data. The research is divided in two parts of analysis which is, Textual Narrative Analysis and Visual Imagery Analysis. The coding theme was used as a guideline in collecting the data. In textual narrative analysis, the result shows that ISIS use 66 times Quran verses, with total 29 different Surah. Besides, 3 new basic theme were developed and 40 sub-themes were identified. In the other side, under visual imagery analysis, the result shows that the total 33 different types of images from Rumiyah has atleast one themes match with the basic theme. The result also shows that all common themes used by the author has a negative tonality and tend to have a favourable toneorientation towards ISIS. Thus, this study shows that content in Rumiyah online magazine is dangerous to be read alone because it will affect one's own faith towards Islamic religion. This magazine use a strategic psychological warfare of propaganda element by manipulating the textual narrative and visual imagery content to disseminate their ideology, inflict fear, influence their targeted audience and to recruits potential followers.